2014
DOI: 10.1177/0894439314563916
|View full text |Cite
|
Sign up to set email alerts
|

Improving Survey Response Rates in Online Panels

Abstract: Identifying ways to efficiently maximize the response rate to surveys is important in surveybased research. However, evidence on the response rate effect of donation incentives and especially altruistic and egotistic text appeal interventions is sparse and ambiguous. Via a randomized survey experiment among 6,162 members of an online survey panel, this article shows how low-cost incentives and cost-free text appeal interventions may affect the survey response rate in online panels. The experimental treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(31 citation statements)
references
References 61 publications
(104 reference statements)
5
24
1
1
Order By: Relevance
“…Although the sample size was small, the response rate of 28% is not atypical of online surveys (Nulty, 2008;Pedersen & Nielsen, 2016). Given the paucity of literature on the subject of social media in child welfare work, these initial results serve not as generalizable population parameters but rather as an important genesis for discussions of this developing topic at the macro level of child welfare policy and training.…”
Section: Discussionmentioning
confidence: 99%
“…Although the sample size was small, the response rate of 28% is not atypical of online surveys (Nulty, 2008;Pedersen & Nielsen, 2016). Given the paucity of literature on the subject of social media in child welfare work, these initial results serve not as generalizable population parameters but rather as an important genesis for discussions of this developing topic at the macro level of child welfare policy and training.…”
Section: Discussionmentioning
confidence: 99%
“…Sauermann and Roach (2013) suggest that the following aspects increase the response rate: personalisation, lottery incentives and customised reminders. While Sánchez-Fernández, Muñoz-Leiva, and Montoro-Ríos (2012) found that personalisation, reminders and incentives did not improve response rates, Pedersen and Nielsen (2016) found that cash price lottery incentives are more effective than altruistic incentives. There are a myriad of techniques to improve the response rate; these will be discussed next.…”
Section: The Challenge Of Rising Nonresponse Ratesmentioning
confidence: 99%
“…Secondary data researchers often do not appreciate the challenges experienced by the originators of the research. However as this secondary analysis is conducted by the originator of the Lottery incentives (Sauermann & Roach, 2013); Cash incentives (Pedersen & Nielsen, 2016); Trading the results of the study (Wright, 2005). Personalisation Generate a sense of community (Petrovčič, Petrič, & Manfreda, 2016); Customise user invitations (Shao, Wu, Zou, & Chen, 2015); Promote a positive researcher identity (Pan, Woodside, & Meng, 2014); Dynamic communication (Garcia, Standlee, Bechkoff, & Cui, 2009); Impression management (Garcia, Standlee, Bechkoff, & Cui, 2009).…”
Section: Research Methodsologymentioning
confidence: 99%
See 2 more Smart Citations